Oral Hygiene and Periodontal Status of Visually Impaired Individuals of a Residential School in Eastern Nepal - Giri, Dhirendra Kumar; Jha, Rajkumar; Bhagat, Tarakant (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Gingival and periodontal diseases are a matter of serious concern in Nepalese population. These diseases may also be present in visually impaired individuals. So, the scientific fact is necessary to unmask this and the pathogenesis behind it.Objective: To assess the oral hygiene and periodontal status of visually impaired individuals of a residential school in Eastern Nepal.Methods: A study was conducted at Gyanchakchu Vidyalaya in Dharan-15. A total of 130 visually impaired individuals (88 males and 42 females) with the mean age of 6-20 years were included in the study. Information regarding oral hygiene practices was gathered through personal interaction by the interviewers. Oral hygiene status was assessed by using Plaque Index of Silness and Loe (1964) and Gingival Index of Loe and Silness (1963) and to assess the periodontal status, Community Periodontal Index was used.Results: A total of 112 (86.2%) participants, brushed their teeth with the help of toothbrush and toothpaste, 101 (77.7%) of them brushed once a day in morning, 83 (63.8%) of the students used horizontal brushing technique and 90 (69.2%) of the students rinsed their mouth after meal. Periodontal and gingival status of visually impaired individual show that majority 90 (69.2%) had no periodontal pocket and 83 (63.8%) had slight loss of attachment.Conclusion: The oral hygiene status and periodontal status of visually impaired individuals can be improved more through an in-service educational programmes